The paradox when managing the riparian zones of rivers with engineered embankments in The French prealps - André Evette; Caroline Zanetti; Paul Cavaillé; Fanny Dommanget; Patrice Mériaux; Michel Vennetier (Revue de Géographie Alpine)
Rivers in the Prealps have undergone considerable embankment and channelization work over recent centuries. The current management of these embankments often excludes woody plants for safety reasons. However, alluvial vegetation and riparian zones can play important ecological roles by providing often very biodiverse environments and acting as biological corridors.There is a paradox when managing these embankments between the security requirement to exclude woody plants and the ecological imperative to add vegetation. Experiments carried out under the Géni’Alp Interreg project in the French and Swiss Prealps have improved our knowledge of both risks to embankments by the root systems of ligneous plants and the impact of creating artificial riverbanks on biodiversity.This article aims to explain this paradox in the light of the results of these experiments. It presents an analysis of the size and spatial extension of the root systems of trees and shrubs extracted from the riverbanks and the embankments of two alpine streams. It also compares the results of findings on the taxonomic diversity of vegetation and ground beetles, as well as the diversity of benthic macrofauna between three types of banks: riprap, bioengineered and ‘natural’. Based on these elements, this paper explores the management tradeoffs faced by river maintenance engineers and offers suggestions on how to meet this dual challenge.